The structure of thermally reduced graphene oxide - Drewniak, Sabina Elżbieta; Muzyka, Roksana; Drewniak, Łukasz (Photonics Letters of Poland, 2020)
The paper focused on the description of the reduced graphene oxide (rGO) structure. This material is obtained from a multistage production process. Each of these stages has a large impact on its structure (the number and type of functional groups, number of defect or the size of the flakes), and this in turn affects its properties. We would like to visualize the reduced graphene oxide, both using a diagram showing the atomic structure, as well as by imaging using scanning electron microscopy (SEM) and atomic force microscopy (AFM). In the paper, the elementary composition of selected elements and data obtained from X-ray photoelectron spectroscopy technique (XPS) will be also presented. Full Text: PDF References X. Peng, Y. Wu, N. Chen, Z. Zhu, J. Liu, and H. Wang, "Facile and highly efficient preparation of semi-transparent, patterned and large-sized reduced graphene oxide films by electrochemical reduction on indium tin oxide glass surface", Thin Solid Films 692, 137626 (2019). CrossRef L. Guo, Y.-W. Hao, P.-L. Li, J.-F. Song, R.-Z. Yang, X.-Y. Fu, S.-Y. Xie, J. Zhao and Y.-L. Zhang, "Improved NO2 Gas Sensing Properties of Graphene Oxide Reduced by Two-beam-laser Interference", Sci. Rep. 8, 1 (2018). CrossRef Y. S. Milovanov, V.A. Skryshevsky, , O.M. Slobodian, , D.O. Pustovyi, X.Tang, J.-P. Raskin, and A.N. Nazarov, "Influence of Gas Adsorption on the Impedance of Graphene Oxide", 2019 IEEE 39th Int. Conf. Electron. Nanotechnology, ELNANO 2019 - Proc. 8783946, CrossRef M. Reddeppa, B.-G. Park, , M.-D. Kim, K.R. Peta, N.D. Chinh, D. Kim, S.-G. Kim, and G. Murali, "H2, H2S gas sensing properties of rGO/GaN nanorods at room temperature: Effect of UV illumination", Sensors Actuators B. Chem. 264, (2018). CrossRef W. L. Xu, C. Ding, , M.-S. Niu, X.-Y. Yang, F. Zheng, J. Xiao, M. Zheng and X.-T. Hao, "Reduced graphene oxide assisted charge separation and serving as transport pathways in planar perovskite photodetector", Org. Electron. 81, 105663 (2020). CrossRef K. Sarkar, M. Hossain, P. Devi, K. D. M. Rao, and P. Kumar, "Self‐Powered and Broadband Photodetectors with GaN: Layered rGO Hybrid Heterojunction", Adv. Mater. Interfaces, 6, 20 (2019). CrossRef S. Pei and H. M. Cheng, "The reduction of graphene oxide", Carbon, 50, 9 (2012). CrossRef R. Muzyka, S. Drewniak, T. Pustelny, M. Chrubasik, and G. Gryglewicz, "Characterization of Graphite Oxide and Reduced Graphene Oxide Obtained from Different Graphite Precursors and Oxidized by Different Methods Using Raman Spectroscopy", Materials 11, 7 (2018). CrossRef M.-H. Tran and H. K. Jeong, "Influence of the Grain Size of Precursor Graphite on the Synthesis of Graphite Oxide", New Phys. Sae Mulli, 63, 2 (2013). CrossRef M.-H. Tran, C.-S. Yang, S. Yang, I.-J. Kim, and H. K. Jeong, "Influence of graphite size on the synthesis and reduction of graphite oxides", Curr. Appl. Phys., 14, SUPPL. 1 (2014). CrossRef N. Sharma, Y. Jain, , M. Kumari, R. Gupta, S.K. Sharma, K. Sachdev, "Synthesis and Characterization of Graphene Oxide (GO) and Reduced Graphene Oxide (rGO) for Gas Sensing Application", Macromol. Symp. 376, 1 (2017). CrossRef M. Wei, L. Qiao, , H. Zhang, S. Karakalos, K. Ma, Z. Fu, M.T. Swihart, G. Wu, "Engineering reduced graphene oxides with enhanced electrochemical properties through multiple-step reductions", Electrochim. Acta, 258 (2017). CrossRef S. Drewniak, M. Procek, R. Muzyka, T. Pustelny, "Comparison of Gas Sensing Properties of Reduced Graphene Oxide Obtained by Two Different Methods", Sensors, 20, 11 (2020). CrossRef L. Li, R.-D. Lv, S. -C. Liu, Z. D. Chen, J. Wang, Y.-G. Wang, W. Ren, "Using Reduced Graphene Oxide to Generate Q-Switched Pulses in Er-Doped Fiber Laser", Chinese Physics Letters, 35, 11 (2018) CrossRef